Psychomotor Skills-Self Renewal Capacity of Students with the PACE Model based on Project Based Learning - Yuliawati Yunus; Suparmi; Silky Safira; Renny Permata Saputri; Monica Fransisca (Universitas Pendidikan Ganesha, 2023)
Psychomotor abilities in students' self renewal capacity are still low in competence in practicing MySQL databases so it is estimated that students have problems in completing the final assignment project in object oriented programming courses. This study aims to improve students' psychomotor abilities in completing their final project through the implementation of the use of the PACE model based on project based learning. PACE is a learning model based on constructiveness with phases: Project, Activity, Cooperative Learning and Exercise, this model is suitable to be combined with project based learning to increase students' self renewal capacity in doing programming practice. This type of research is descriptive with a qualitative approach. There were 23 students of the Informatics Engineering Education study program as the subject of this research. The results showed that the average score of students' psychomotor skills is 81,2% with very good criteria. Then Self renewal capacity shows a percentage of 71.7% with good criteria. In conclusion, the application of the PACE model based on Project Based Learning in object-oriented programming courses can be an alternative to increase self-renewal capacity in students' psychomotor abilities.